Internal combustion engine provided with variable compression ratio mechanism - TANAKA HIROYUKI (2015)
This internal combustion engine provided with a variable compression ratio mechanism is equipped with a turbocharger, the opening degree of a wastegate valve is controlled to a target opening degree for each engine operating state (step 103), and when the mechanical compression ratio is changed (step 111), the target opening degree of the wastegate valve for the current engine operating state is revised (step S114).